Benzoxazine Resin/Carbon Nanotube Nanostructured Composite's Degradation Kinetic - Untem, Flavia O. [UNESP]; Botelho, Edson C. [UNESP]; Rezende, Mirabel C.; Costa, Michelle Leali [UNESP] (Amer Scientific Publishers, 2014)
In the last decades a new class of thermoset phenolic resin is emerging as a substitute of the traditional epoxy and phenolic resins in the aircraft industry. This new class is called polybenzoxazines and its associates the epoxy resin's mechanical properties and phenolic resin's thermal and flame retardant properties, resulting in a resin with superior properties when analyzed with the others singly. The introduction of carbon nanotubes in low concentration into polymeric matrices can produce nanostructured materials with good properties. Thus, in this study, nanostructured composites of benzoxazine resin were processed with different concentration of carbon nanotubes (0.1%, 0.5% and 1.0% w/w). In order to evaluate the thermostability of the benzoxazine resin and its nanostructured composites, it was performed a degradation kinetic study using the thermogravimetric technique. For that, the analysis have been done with the temperature ranging from 25 degrees C to 1000 degrees C at nitrogen atmosphere (100 mL . min(-1)) and in different heating rates (2, 4, 6, 8, 10 and 20 degrees C . min(-1)), in order to obtain the kinetic parameters (activation energy, E-a, and pre-exponential factor, A), based on Ozawa-Wall-Flynn model. The results showed excellent agreement between the thermogravimetric curves obtained and the Ozawa-Wall-Flynn method. The degradation kinetic study showed that the introduction of carbon nanotubes in the benzoxazine matrix does not change the thermostability of the resin, so that it does not have a significant influence in the shelf life of the material.
Keywords: Degradation Kinetic; Benzoxazine Resin; Carbon Nanotubes; Thermogravimetric; Shelf-Life